UNIVERSAL TOOL FOR DATA ANALYSIS (Perner's Contacts, 2016)
This article describes the main parts of an open and universal data analysis software TeleMatrix V3 based on MATLAB. It helps simplify and speed up most of the processes of the measurement data evaluation.
Keywords: data analysis; telemetry; Matlab